Future trends in synthetic biology in Asia. Issue 1 (5th March 2021) - Mao, Ning; Aggarwal, Nikhil; Poh, Chueh Loo; Cho, Byung Kwan; Kondo, Akihiko; Liu, Chenli; Yew, Wen Shan; Chang, Matthew Wook
Abstract: Synthetic biology research and technology translation has garnered increasing interest from the governments and private investors in Asia, where the technology has great potential in driving a sustainable bio‐based economy. This Perspective reviews the latest developments in the key enabling technologies of synthetic biology and its application in bio‐manufacturing, medicine, food and agriculture in Asia. Asia‐centric strengths in synthetic biology to grow the bio‐based economy, such as advances in genome editing and the presence of biofoundries combined with the availability of natural resources and vast markets, are also highlighted. The potential barriers to the sustainable development of the field, including inadequate infrastructure and policies, with suggestions to overcome these by building public‐private partnerships, more effective multi‐lateral collaborations and well‐developed governance framework, are presented. Finally, the roles of technology, education and regulation in mitigating potential biosecurity risks are examined. Through these discussions, stakeholders from different groups, including academia, industry and government, are expectantly better positioned to contribute towards the establishment of innovation and bio‐economy hubs in Asia. Abstract :